The Affect and its Image in Gilles Deleuze’s Philosophy - Dinić Miljković, Vesna (Collection of Papers of the Faculty of Philosophy in Priština, 2021)
There is no perception without affection. This necessity comes from the very fact that perception measures our possible action upon things, and thereby, the possible action of things upon us. For the French philosopher Gilles Deleuze, affection occupies exactly this gap between the potentiality of action of the perceived objects and our virtual action upon them. This encounter between the affected body and the affecting body presumes the in-betweenness, an interval between a perception which is troubling in certain respects and a hesitant action. As opposed to emotion, which is directed toward a certain goal and demands actualization, affect precedes will, as a pre-personal intensity referring to the passage from one experiential state of the body to another. Influenced by Baruch Spinoza’s concept of affect and Henri Bergson’s thesis on movement that he considers the essence of cinema’s movement-image, Deleuze creates his own theory of affect that finds its most obvious manifestation in the works of art. The artist creates affects, gives them to us, draws us into the compound, and makes us become with them. Deleuze’s aesthetics produces the spectator’s movement in-place through sensation. Through shapes and colours, the canvas vibrates, clenches or cracks open because it is the bearer of glimpsed forces. Like with Edward Munch’s The Scream or Francis Bacon’s Portrait of Pope Innocent X, the invisible forces become visible in themselves and thus the sensation becomes materialized right there on the canvas surface. In cinema, this materialization of sensation Deleuze recognized in the affection-image, abstracted from the causal and spatio-temporal relations to the images that surround it, and therefore open to a spiritual dimension. As power-quality, the affect gains its independence from the thing that expresses it and becomes an entity, a potentiality considered to itself.
Keywords: Gilles Deleuze; affect; affection-image; cinema; art